2020
DOI: 10.1186/s12974-020-01875-5
|View full text |Cite
|
Sign up to set email alerts
|

CCL2/CCR2 system in neuroepithelial radial glia progenitor cells: involvement in stimulatory, sexually dimorphic effects of maternal ethanol on embryonic development of hypothalamic peptide neurons

Abstract: Background: Clinical and animal studies show that alcohol consumption during pregnancy produces lasting behavioral disturbances in offspring, including increased alcohol drinking, which are linked to inflammation in the brain and disturbances in neurochemical systems that promote these behaviors. These include the neuropeptide, melanin-concentrating hormone (MCH), which is mostly expressed in the lateral hypothalamus (LH). Maternal ethanol administration at low-to-moderate doses, while stimulating MCH neurons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Notably, embryonic exposure of zebrafish to EtOH in the water at low-moderate doses has similar behavioral effects 14 to those produced by prenatal exposure to EtOH in rodents 15 and humans 7 . Moreover, these behavioral effects in zebrafish as well as rats are accompanied by an increase in number of developing neurons in the hypothalamus 16 , specifically neurons that express orexigenic peptides known to promote alcohol consumption 11 , 13 , 17 , 18 , and also an increase in radial glia progenitor cells and microglia in the hypothalamus 19 , indicating that EtOH has stimulatory effects on diverse cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, embryonic exposure of zebrafish to EtOH in the water at low-moderate doses has similar behavioral effects 14 to those produced by prenatal exposure to EtOH in rodents 15 and humans 7 . Moreover, these behavioral effects in zebrafish as well as rats are accompanied by an increase in number of developing neurons in the hypothalamus 16 , specifically neurons that express orexigenic peptides known to promote alcohol consumption 11 , 13 , 17 , 18 , and also an increase in radial glia progenitor cells and microglia in the hypothalamus 19 , indicating that EtOH has stimulatory effects on diverse cell types.…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by studies in rodents, demonstrating that chemokines are expressed in Hcrt and Mch peptide neurons and that prenatal alcohol exposure similarly increases chemokine co-expression within these neurons [49,176]. Also, prenatal administration of the chemokines themselves mimics the alcohol-induced increase in peptide expression, while administration of chemokine neutralizing antibodies or antagonists prevents these effects of alcohol [255]. In another study of zebrafish [6], we tested the involvement of this chemokine system in the effects of embryonic alcohol exposure on the location of Hcrt neurons, and found that pretreatment with a Cxcr4 antagonist prevents the alcohol-induced formation of ectopic Hcrt neurons further toward the anterior in the preoptic area.…”
Section: Brain Mechanisms Underlying Neuronal Disturbances In Zebrafishmentioning
confidence: 67%
“…This chemokine is known to be highly expressed in the obese state and is closely associated with the intake of a HFD (157), with genetic deletion or pharmacological blockade of its receptor, C-C chemokine receptor 2 (CCR2), to reverse or eliminate HFD-induced effect (158). This chemokine has much broader range in the brain due to its diverse co-expression with neuropeptides in several brain areas, including the hypothalamus and thalamus (159)(160)(161), and in developmental studies with other substances of abuse reveal close association with migratory radial glial cells (161). If the CCR2 receptor is centrally blocked by an antagonist, weight-loss induction by triggering foreign molecule inflammation through lipopolysaccharide injection is blocked (162), suggesting reduced brain activity of the CCR2 receptor may contribute to increased dietary fat intake and subsequent weight gain.…”
Section: Modulation and Development Of Hypothalamic Peptide Neurons Bmentioning
confidence: 99%